Optimizing routes using the vehicle routing problem - Benmansour, Soufiane (2022)
With the emergence of e-commerce and its significant growth during the COVID-19 pandemic, more people aim to ship their products as fast as possible. More organizations such as DHL and USPS invest vast amounts of money in minimizing transportation costs while finding the shortest route that the delivery man should take to reach different destinations. My Work Project will evolve around studying the Vehicle Routing Problem that uses different algorithms to find the shortest route depending on various constraints. This project will include four parts: a literature review expressing an overview of the vehicle routing issue; then a state of the art of algorithm to understand the meaning behind the main algorithms. Finally, build a code (coding platform) using the algorithms discussed previously to solve a situation for the traveling salesman person and VRP.